High-value data product and replicable analytic pipeline for cross-cutting research, demonstrating value of Open and FAIR data: Profitability of fertilizer use in Africa - CGIAR Platform for Big Data in Agriculture (2020)
The code for the analytic pipeline, associated data, and description of analysis have been submitted to a peer-reviewed publication. As of end of 2020 the submission was still being reviewed.